Strategy for Developing Discipline Character in Vocational High School - Halimah, Nur; Muhyidin; Atim Rinawati; Umi Arifah; Imam Subarkah; Siti Fatimah (Mataram University, 2025)
The aim of this research is to analyze the implementation of discipline character development at vocational high school. This study employs a qualitative approach of the phenomenological type. The research was conducted at SMK Negeri 1 Puring, Kebumen. The subjects of this study include the principal, teachers, staff, and students. Data collection techniques used are interviews, observations, and document studies. Triangulation techniques were applied to ensure data validity. Data analysis follows the Miles & Huberman & Saldana model. The results of the study indicate that the implementation of discipline character development at SMK Negeri 1 Puring involves systematic steps, including the formulation of school regulations, daily guidance, extracurricular activities, leadership and self-development programs, classroom learning, technology utilization, parental involvement, monitoring and evaluation, and fostering a school culture. Collaboration among all stakeholders, such as parents and the community, is crucial in instilling discipline character in students.